Trends of Arabic Language Teachers in the Secondary Stage towards Homework (Journal Of Educational and Psychological Researches, 2022)
The problem of the research is indicated by answering the following questions: 1) what are the attitudes of the Arabic language teachers towards homework? 2) Do the Arabic language teachers differ in their attitudes towards homework according to their specialization? 3) Do the Arabic language teachers differ in their attitudes towards homework according to their gender (male and female)? According to the three questions asked above, we may state the following hypotheses. There is no statistically significant difference between the average of the marks of Arabic language teachers in the real practice of the scale of the attitudes towards their homework and their average in the hypothetical practice of the scale, which is expected (0.05). 2-There is no statistically significant difference between the averages of Arabic language teacher’s marks in the scale of the attitudes towards homework in term of specialization at (0.05). The sample of the research consists of (986) teachers (male and female), (540) are male and (446) are female teachers of Arabic language at secondary schools in Baghdad city. In order to make sure of the hypothesis of the research, the researcher has prepared a scale to measure the Arabic language teachers’ attitudes towards homework. The scale consists of (50) items, (24) are negative items and (26) positive. The results revealed that the Arabic language teachers have positive attitudes towards homework; the attitudes of the Arabic language female teachers towards homework are higher compared to male teachers.According to the results of the research, the researcher has come out with some recommendations and suggestions.